The Psychological Needs of Gifted Children: Addressing Asynchronous Development and Social-Emotional Challenges - Rahman, Imam Aulia; Chai, Napat; Som, Rit (Research Psychologie, Orientation et Conseil, 2025)
Gifted children often exhibit asynchronous development, where cognitive, emotional, and social growth occur at uneven rates, creating complex psychological needs that are frequently misunderstood in educational and familial contexts. This developmental asynchrony may result in social-emotional vulnerabilities such as heightened sensitivity, perfectionism, and difficulties in peer relationships. The study aims to explore the psychological needs of gifted children with a focus on addressing the impact of asynchronous development on their social-emotional well-being. A qualitative research design employing phenomenological analysis was utilized to examine the lived experiences of 25 gifted students aged 8–14, selected from specialized education programs. Data were collected through in-depth interviews, behavioral observations, and teacher reflections, followed by thematic coding. The results revealed three major themes: (1) emotional intensity as both a strength and source of distress, (2) social incongruence and peer isolation resulting from developmental disparities, and (3) the need for adaptive counseling and differentiated emotional support. The study concludes that educational and psychological interventions must be tailored to the unique developmental trajectories of gifted children, emphasizing emotional regulation, self-concept development, and social integration. Understanding asynchronous growth is essential for fostering balanced psychological and academic development among gifted learners.